The Relationship between Social Adaptation and Homesickness of Cadets in Politeknik Pelayaran Barombong - Irwan Jaya (PINISI Discretion Review, 2022)
This research aims to understand if there are any relationship between social adaptation and homesickness. The variables of this research will be Social Adaptation as free variables and Homesickness as bound variables. The population of this research will be 53 cadets in Politeknik Pelayaran Barombong, Analysis method that is going to be used in this research will be the correlation of Product Moment by Pearson. Based on the analysis result it is found that value of coefficient correlation as much as -0.335 along with the Sig value as much as 0.014 < 0.05. Thus, shows that there are significant relationship between both variables. Furthermore, coefficient correlation value resulted as negative, means that the relationship between both variables are contradicting one another. This also means the higher social adaptivity that certain individual has, homesickness will have a lower possibility to be happened.